The frequency of cigarette smoking, alcohol and nonalcoholic substance use and the relationship with axis-i diagnoses in vitiligo and chronic urticaria patients - Sukan, Meltem; Maner, Fulya (Journal of Dependence, 2005)
Objective: The aim of this study was to investigate the frequency of using of cigarette smoking, alcohol and nonalcoholic substance among the patients with vitiligo and chronic urticaria which are skin disorders having psychosomatic aspects and stress sensitivity.Method: The sample was composed of 50 vitiligo and 50 chronic urticaria patients recruited from the Dermatology policlinics of four major hospitals in Istanbul. The patient groups were compared with 50 healthy controls. The age range of the patient and control groups was 16-60 years.Results: 48% of vitiligo group, 68% of chronic urticaria group, 50% of control group were females. Cigarette smoking was 58% in vitiligo group, 40% in urticaria group, 36% in control group; alcohol intake as social drinking was 32% in vitiligo group, 20%in chronic urticaria group, 32% in control group; alcohol abuse was 2% in vitiligo group, 4% in urticaria group; substance abuse was 2% in vitiligo group only. There is no statistically significant difference between the groups according to the frequency of cigarette smoking and alcohol and nonalcoholic substance use.Conclusion: There is no difference in cigarette smoking and alcohol and nonalcoholic substance use between vitiligo, chronic urticaria patients and control group. It is clear that dermatologists and psychiatrists should cooperate to relieve the tension of these groups of patients.
Keywords: Vitiligo; chronic urticaria; cigarette smoking; alcohol; nonalcoholic substance